2020
DOI: 10.1016/j.agee.2019.106790
|View full text |Cite
|
Sign up to set email alerts
|

Water sources for root water uptake: Using stable isotopes of hydrogen and oxygen as a research tool in agricultural and agroforestry systems

Abstract: Understanding water sources for crop water uptake in agricultural and agroforestry systems is an essential step to develop more efficient and sustainable water management strategies, which is increasingly important in the light of current world population growth, changing climatic conditions and consequent growing pressures on agricultural-and agroforestry production. Stable isotopes of hydrogen and oxygen in the water molecule are powerful and, nowadays, affordable tracers that can help to define the proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 86 publications
3
45
0
Order By: Relevance
“…It is likely that the fractionation observed in the plant water collected in this study represents fractioned soil water that was consumed by the plants. This is consistent with results observed in previous studies using stable water isotopes to map out plant water sources (Brooks et al, 2010;Penna et al, 2020;Sprenger et al, 2016). Further, this interpretation of plant water composition is supported by plant water samples falling along the theoretical evaporation lines estimating how soil water would evolves isotopically due to evaporation.…”
Section: Temporally Variable Plant Water Sourcessupporting
confidence: 91%
See 1 more Smart Citation
“…It is likely that the fractionation observed in the plant water collected in this study represents fractioned soil water that was consumed by the plants. This is consistent with results observed in previous studies using stable water isotopes to map out plant water sources (Brooks et al, 2010;Penna et al, 2020;Sprenger et al, 2016). Further, this interpretation of plant water composition is supported by plant water samples falling along the theoretical evaporation lines estimating how soil water would evolves isotopically due to evaporation.…”
Section: Temporally Variable Plant Water Sourcessupporting
confidence: 91%
“…Despite that stable isotopes have been used to a lesser extent in agricultural systems than in natural systems to investigate plant water sources (Penna et al, 2020), there are successful studies done in coffee (Muñoz-Villers et al, 2020), maize, wheat (Stumpp et al, 2009) and rice cultures (Mahindawansha et al, 2018;Shen et al, 2015). In the case of rice, Shen et al (2015) observed that flooded rice consumed soil water from 0-15 cm deep, while Mahindawansha et al (2018) found that upland rice in dry conditions mostly consumed soil water from up to 50 cm deep except during the maturing stage, when plants shifted to use water from the 10-30 cm soil depth.…”
Section: Introductionmentioning
confidence: 99%
“…Shifts in root water uptake patterns due to eCO 2 typically depend on the growth stage [31]. For the current treatment at the seedling stage, roots mainly took up soil water from the surface layer (0−20 cm) [23,24,26].…”
Section: Impacts Of Eco 2 On Crop Water Uptakementioning
confidence: 90%
“…Most of the previous studies have determined the main root water uptake depth of maize and its seasonal variability among various irrigation and fertilization strategies. Maize across the globe was identified to primarily absorb shallow soil water (mostly at the upper 20 cm depth), particularly during the vegetative and mature stages [4,31]. Soil water in deep layers (even more than 120 cm) could be taken up by maize during the silking and milking stages [26].…”
Section: Introductionmentioning
confidence: 99%
“…The development of low-cost and easy-to-use spectroscopic techniques for the collection and isotopic analysis of water samples at a high temporal resolution (e.g., Kerstel et al, 1999;Penna et al, 2010;von Freyberg et al, 2017) stimulated the application of stable isotopes to investigate the water fluxes in the soil-plant-atmosphere continuum (Brooks et al, 2010;McDonnell, 2014). An increasing number of new studies has been conducted to better understand water dynamics, such as water uptake and evapotranspiration partitioning, in the soil-plant-low atmosphere continuum in different climates and in both natural (e.g., Allen et al, 2019;Dubbert et al, 2019;Liu et al, 2019a;Oerter et al, 2019;Qiu et al, 2019) and managed (agricultural and agroforest) (e.g., Liu et al, 2019b;Quade et al, 2019;Zhang et al, 2019;Penna et al, 2020) environments. Compared to the rapid increase of the number of studies using a stable isotope approach, only a small fraction of them focused on the comparison of two or more soil or plant water extraction techniques (Sprenger et al, 2015;Orlowski et al, 2016b;Millar et al, 2018;Fischer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%